2014
DOI: 10.1021/es501353x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tracer Method To Measure Isotopic Labeled Gas-Phase Nitrous Acid (HO15NO) in Biogeochemical Studies

Abstract: Gaseous nitrous acid (HONO), the protonated form of nitrite, contributes up to ∼60% to the primary formation of hydroxyl radical (OH), which is a key oxidant in the degradation of most air pollutants. Field measurements and modeling studies indicate a large unknown source of HONO during daytime. Here, we developed a new tracer method based on gas-phase stripping-derivatization coupled to liquid chromatography-mass spectrometry (LC-MS) to measure the 15N relative exceedance, ψ(15N), of HONO in the gas-phase. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…Here, we compare our results to studies which applied the same method (with the same or very similar conditions). The emission rates are consistent with these studies where HONO-N or NO-N emissions from soil between 1-3000 ng m -2 s -1 were found (Su et al, 2011;Oswald et al, 2013;Mamtimin et al, 2016;Wu et al, 2014;Weber et al, 2015). Mamtimin et al (2016) observed NO-N fluxes at 25°C of 57.5 ng m -2 s -1 , 18.9 ng m -2 s -1 and 4.1 ng m -2 s -1 for soil of grape and cotton fields and desert soil from an oasis in China, respectively.…”
Section: No and Hono Flux Measurementssupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we compare our results to studies which applied the same method (with the same or very similar conditions). The emission rates are consistent with these studies where HONO-N or NO-N emissions from soil between 1-3000 ng m -2 s -1 were found (Su et al, 2011;Oswald et al, 2013;Mamtimin et al, 2016;Wu et al, 2014;Weber et al, 2015). Mamtimin et al (2016) observed NO-N fluxes at 25°C of 57.5 ng m -2 s -1 , 18.9 ng m -2 s -1 and 4.1 ng m -2 s -1 for soil of grape and cotton fields and desert soil from an oasis in China, respectively.…”
Section: No and Hono Flux Measurementssupporting
confidence: 90%
“…The dynamic chamber method for analyzing NO and HONO emissions from soil samples was already introduced before (Oswald et al, 2013;Weber et al, 2015;Wu et al, 2014 and water vapor were quantified. HONO was analyzed with a commercial long path absorption photometer (LOPAP, QUMA GmbH; Wuppertal, Germany), with a detection limit of ~4 ppt and 10% uncertainty (based on the uncertainties of liquid and gas flow, concentration of calibration standard and regression of calibration).…”
Section: Trace Gas Exchange Measurementsmentioning
confidence: 99%
“…Here, we compared our results to studies that applied the same method (with the same or very similar conditions). The emission rates were consistent with the studies in which HONO-N or NO-N emissions from soil between 1 and 3000 ng m −2 s −1 were found (Su et al, 2011;Oswald et al, 2013;Mamtimin et al, 2016;Wu et al, 2014;Weber et al, 2015). Mamtimin et al (2016) observed NO-N fluxes of 57.5, 18.9 and 4.1 ng m −2 s −1 at 25 • C for soil of grape and cotton fields and desert soil from an oasis in China, respectively.…”
Section: No and Hono Flux Measurementssupporting
confidence: 90%
“…The dynamic chamber method for analyzing NO and HONO emissions from soil samples was already introduced before (Oswald et al, 2013;Weber et al, 2015;Wu et al, 2014) and in general showed good agreement with flux measurements in the field (van Dijk et al, 2002;Rummel et al, 2002). Under the prevailing dry and hot conditions in Cyprus, macropores and cracks are likely to be present in the soil layer.…”
Section: Trace Gas Exchange Measurementsmentioning
confidence: 80%
“…Further investigations comprising multiple nitrogen compounds and isotopes should unravel the interplay of different chemical and biological species and processes in the cycling of nitrogen by biocrusts (33)(34)(35)(36).…”
Section: Resultsmentioning
confidence: 99%